Reactive Power Compensation for Non-Traction Railway Consumers (preprint) - Mukha, Andrii M.; Bondar, Oleh I. (Institut Kolejnictwa, 2020)
ENG: This paper deals with the problems of power supply efficiency for non-traction railway customers. Unlike public distribution networks, the non-traction power supply network is within the zone of influence of electromagnetic fields and the conductive influence of the distorted traction current. As a result, poor power quality and additional losses are typical for non-traction railway networks. Subsequently, conflicts due to the low quality of electricity may arise between the railway and its customers powered by the distribution networks of the railway. The influence of a reactive power compensation device on the voltage drop in a non-traction power line is investigated in the article. The implementation of reactive power compensation allows voltage losses during its transmission to the final consumer to be reduced by almost 5% and electricity losses by 3%.

UKR: У цій роботі розглядаються проблеми ефективності енергопостачання нетягових споживачів залізниць. На відміну від розподільних мереж загального користування, мережа нетягового електропостачання знаходиться в зоні впливу електромагнітних полів а також кондуктивного впливу спотвореного тягового струму. В результаті для нетягових залізничних мереж характерні низька якість електроенергії та наявність її додаткових втрат. Отже може виникати несумісність між нетяговими споживачами, які отримують живлення від розподільних мереж залізниці та системою тягового електропостачання через низьку якість електроенергії. У статті досліджується вплив встановлення пристрою компенсації реактивної потужності на втрати напруги в нетяговій лінії електропередачі. Показано, що реалізація компенсації реактивної потужності дозволяє знизити втрати напруги при її передачі кінцевому споживачеві майже на 5% і втрати електроенергії на 3%.
Компенсація реактивної потужності не тягових споживачів залізничного транспорту (препринт)
A. Mukha: ORCID 0000-0002-5629-4058, O. Bondar: ORCID 0000-0003-3884-5589
Keywords: non-traction consumer; power factor corrector; reactive power compensator; graph of electric network; nodal analysis; нетяговий споживач; коректор коефіцієнта потужності; пристрій компенсації реактивної потужності; граф електричної мережі; метод вузлових потенціалів; КТЕМ